KREATIVITAS RAHAYU SUPANGGAH PADA FILM OPERA JAWA KARYA GARIN NUGROHO - Salim, Muhammad Nur (Institut Seni Indoensia Surakarta, 2020)
ABSTRACT One of the developments in film in Indonesia is the musical genre film. This genre film experienced a post-reform high point when Sherina's Adventure Film came. This point then became the beginning of the development of musical genre films that were born in the 2000s period. One of the interesting musical films is the Javanese Opera Film by Garin Nugroho. Opera Jawa is interesting because first, Opera Jawa has received various awards and nominations at both national and international levels. Second, because this film bases its musical work on Javanese gamelan or gamelan media. This second reason is the focus of this research. The research